TINGKAT KONFORMITAS MAHASISWA BIMBINGAN DAN KONSELING STKIP PGRI SUMATERA BARAT - Susri, Yelni; Kasih, Fitria; Yulastri, Weni (Bimbingan dan Konseling, 2013)
Observations result through, students force themselves to follow trends such as: often change the handphone, exaggerated dress, lingerie model, students with a speaking style that candidates should not educators or guidance counselor. Also found students more obedient to the friends group, so that they can be accepted in the group. This research is a descriptive study attempted to describe the situation as it is. The study population was all students of Force Guidance and Counseling, 2009, 2010 and 2011 STKIP PGRI West Sumatra, a population of as many as 846 people. Samples were selected by proportional stratified random sampling technique, sampling of members of the population at random and stratified proportionally. Sample was 89 students guidance and counseling, using questionnaire data collection, statistical analysis used is descriptive by using a percentage formula. The results showed: 1) The level of conformity blind student guidance and counseling STKIP PGRI West Sumatra can categorized as high, 2) The level of conformity internalization Guidance and Counselling students STKIP PGRI West Sumatra in general can be categorized as high, and 3) The level of conformity internalization of student guidance and counseling STKIP PGRI West Sumatra is generally categorized as high. Observations result through could see that the level of conformity student guidance and counseling, including high and should be reduced for the foreseeable future